Research case of landslide and simulation using finite element method - Mohd Zuhaidi Bin Zainol Abidin (School of Environmental Engineering, University Malaysia Perlis, 2014)
Massive landslides in Malaysia are mainly attributed to frequent and prolonged rainfalls, in many cases associated with monsoon seasons. Of the landslide prone areas in Malaysia, Bukit Antarabangsa area has received the most publicity. A landslide has happened at Bukit Antarabangsa on 6th December 2008.